2016
DOI: 10.1130/g37927.1
|View full text |Cite
|
Sign up to set email alerts
|

A matter of minutes: Breccia dike paleomagnetism provides evidence for rapid crater modification

Abstract: During an impact event, a crater's transient structure adjusts gravitationally. Within medium-sized complex craters, a central uplift rises and collapses resulting in large-scale rotations of the target rock. Estimated crater modification rates from numerical models indicate that complex impact craters modify to a structurally stable state within tens of seconds to several minutes after excavation. However, there is little direct geologic evidence constraining these rates. We show how paleomagnetic measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Such a timing of impact acquisition has been shown for clastic breccia dikes within the Slate Island impact structure (Fairchild et al. ). However, because frictional heating in the breccia dikes is very localized (Fairchild et al.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Such a timing of impact acquisition has been shown for clastic breccia dikes within the Slate Island impact structure (Fairchild et al. ). However, because frictional heating in the breccia dikes is very localized (Fairchild et al.…”
Section: Discussionmentioning
confidence: 66%
“…It has been shown that impact‐related tilting occurs quite rapidly, taking place over a time scale shorter than several minutes in midsized impact craters (Fairchild et al. ). Therefore, the impact breccia is expected to carry a thermoremanent magnetization acquired when the breccia cooled following impact‐related tilting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations